Value Chains of Carrot Commodity on Suthomadansih Agropolitan Area in Karanganyar Regency - Dwi Feri Yatnanto; Indah Susilowati (Jurnal Wilayah dan Lingkungan, 2015)
In 2007, the Central Java Province Government started the implementation of agropolitan program in some regencies with agriculture sector potentialities. The program promoted Suthomadansih Agropolitan Area establishment in Karanganyar Regency. One of the leading commodities from Suthomadansih was carrot. Carrot was considered in the program through infrastructure provision and community development programs. The objectives of the research are to investigate the value chain of carrot commodity in Suthomadansih, and to analyze how the implementation of the agropolitan program is likely to support its value chain. In doing so, there are three indicators that will be identified: the development of supporting infrastructure, agribusiness system, and human resource (Iqbal & Iwan, 2009). Both qualitative and quantitative analyses applied in the study with the performance table of the implementation of the agropolitan program and value chain analysis as the analytical tool. Referred to the value chain analysis of carrot commodity in Suthomadansih, some agropolitan-related development programs from the local government were conducted from the upstream to downstream flows of carrot commodity. However, some programs failed to support the value chain of carrot so that its improvement could not be optimized including Agribusiness Sub Terminal, Worta Cluster, Vitmaka, and Farm Road Improvement Program. The implementation of the agropolitan program was not sustainable because of the absence of the local government budget support. The program was only implemented for three years (2007-2009) so that there were no significant effects of the program on the agricultural sector, especially for carrot commodity.